سوق العمل لخریجى اقسام المکتبات والمعلومات بمحافظة القلیوبیة : دراسة میدانیة لمدى وفاء مقررات قسم المکتبات والمعلومات بجامعة بنها للمهارات المطلوبة - د. منال جابر عکاشة (المجلة الدولية لعلوم المكتبات والمعلومات)
The study provides a picture of the reality of the labor market in Qaliubiyaand the needs of this market of graduates libraries sections, and evaluation ofcourses offered by the Department of Libraries in Benha university depending onthe opinions of alumni and employers, leading to update those decisions inproportion to the actual needs market-based study, thus linking necessary tohappen between the academic institution and potential professional institutionsthat employs graduates of the institution, as well as to identify the labor marketrequirements on survey methodology which is based on a survey of public andprivate institutions that have libraries or those that are likely to need to graduatesqualified to deal with libraries and information sources, as well as access topotential graduates in their work places, as based on the curriculum contentanalysis to analyze the requirements of the labor market in the field of library andinformation in Qaliubiya, and analysis of the list of library and informationdepartment and its programs of study.Amounted courses specialized in the list of libraries at the University ofBanha 41 planned by 84% of the total courses, while the extra-curriculum 8decisions by 16%, and we note that the views of graduates in subjects that havenot useful of which were on top of the Persian language and writing in Arabic andachieve manuscripts and publishing academic. This and there is no writtendescription of the content of these courses or to determine the level and methodof treatment,When asked for materials that have not been addressed in the curriculumare the annual inventory, records, exhibitions, financial affairs - can be taught inthe subjects management and building material and the development of holdings-, office of Education, Educational Psychology and is especially for those whowork and school libraries important, practical training for the lack of All graduatesof the actual practice to work with libraries, programming, databases, electroniclibrary, a material that lacks technical courses in the standard list.